Perancangan Alat Catch Pot Menggunakan Penutup Fleksibel Pada Metode Vacuum Infusion Untuk Membentuk Composite - Arifin, Ronald Akbar; Utama, Firman Yasa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Abstract: This This study aims to explore the process of designing a catch pot to collect excess resin, which previously lacked a cover in the vacuum infusion method used for carbon fiber production, thereby complicating maintenance procedures. The research method employed is Research and Development (R&D), which ensures that the developed tool is both innovative and functional. The R&D process includes stages of design, fabrication, and functional testing. The resulting catch pot measures 20 cm × 20 cm × 20 cm and features a cover equipped with a pressure gauge and a 19 cm metal support to prevent deformation. To ensure a secure seal, silicone sealant and two locking clamps are added on each side of the lid. Two holes with a diameter of 16 mm were created to mount nipples on both sides of the catch pot, connecting to pneumatic hoses sized 10 × 6.5 mm. The catch pot is capable of reaching a vacuum pressure of up to -0.94 bar. Experimental testing using a mud guard specimen showed that the original mud guard weighed 50 grams, while the carbon fiber version produced three times resulted in a lighter average weight of 33 grams, or 33.33% less. These results indicate that the developed catch pot improves the efficiency and maintainability of the vacuum infusion process for carbon fiber fabrication.